A hybrid approach to metamorphic cryptography using KIMLA and DNA concept. Issue 4 (13th August 2019) - Yadav, Vikash; Gupta, Indresh Kumar
Increasing dependency on digital data in today's word required security in term of digital language. Some researcher advocates the use of cryptography to cope the required demand. On the other hand side some researcher advocate the use of steganography. Beauty of cryptography lies in the fact that o/p i.e., encrypted message is difficult to decode if key is unknown. On the other hand beauty of steganography lies in the fact that, secret message is hidden in such a way that it does not attract the attention of unauthorised user. In the proposed work, an effort has been made to fertilise the strength of both concept i.e., steganography and cryptography. DNA concept is used for encrypting the secured text. For hiding the message KIMLA algorithm is used. Implementation results shows that proposed algorithm is efficient in terms of providing security (robustness, payload capacity, etc.).